Oxidized Phospholipids on Lipoprotein(a) Elicit Arterial Wall Inflammation and an Inflammatory Monocyte Response in Humans - van der Valk, Fleur M; Bekkering, Siroon; Kroon, Jeffrey; Yeang, Calvin; Van den Bossche, Jan; van Buul, Jaap D; Ravandi, Amir; Nederveen, Aart J; Verberne, Hein J; Scipione, Corey; Nieuwdorp, Max; Joosten, Leo A B; et al. (Circulation (New York, N.Y.), 2016)
Elevated lipoprotein(a) [Lp(a)] is a prevalent, independent cardiovascular risk factor, but the underlying mechanisms responsible for its pathogenicity are poorly defined. Because Lp(a) is the prominent carrier of proinflammatory oxidized phospholipids (OxPLs), part of its atherothrombosis might be mediated through this pathway. In vivo imaging techniques including magnetic resonance imaging, (18)F-fluorodeoxyglucose uptake positron emission tomography/computed tomography and single-photon emission computed tomography/computed tomography were used to measure subsequently atherosclerotic burden, arterial wall inflammation, and monocyte trafficking to the arterial wall. Ex vivo analysis of monocytes was performed with fluorescence-activated cell sorter analysis, inflammatory stimulation assays, and transendothelial migration assays. In vitro studies of the pathophysiology of Lp(a) on monocytes were performed with an in vitro model for trained immunity. We show that subjects with elevated Lp(a) (108 mg/dL [50-195 mg/dL]; n=30) have increased arterial inflammation and enhanced peripheral blood mononuclear cells trafficking to the arterial wall compared with subjects with normal Lp(a) (7 mg/dL [2-28 mg/dL]; n=30). In addition, monocytes isolated from subjects with elevated Lp(a) remain in a long-lasting primed state, as evidenced by an increased capacity to transmigrate and produce proinflammatory cytokines on stimulation (n=15). In vitro studies show that Lp(a) contains OxPL and augments the proinflammatory response in monocytes derived from healthy control subjects (n=6). This effect was markedly attenuated by inactivating OxPL on Lp(a) or removing OxPL on apolipoprotein(a). These findings demonstrate that Lp(a) induces monocyte trafficking to the arterial wall and mediates proinflammatory responses through its OxPL content. These findings provide a novel mechanism by which Lp(a) mediates cardiovascular disease. URL: http://www.trialregister.nl. Unique identifier: NTR5006 (VIPER Study).